Rancang Bangun Sistem Informasi Aplikasi Sales Report Berbasis Web - Desy Apriani; Rismawan Syaiful Anwar; Robby Al Hamzah (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
The development of technology is currently considered very rapidly developing, especially in the industrial field. Competition in the industrial world is getting tougher so that the company will always try to continue to be the first in satisfying the company's partners so they do not switch to another. In carrying out reporting, Sales Report still uses office-based applications, namely Microsoft Excel, which results in suboptimal performance results. Then a web-based Sales Report application system was built. In determining research and research design requires a method to see the development of the design and research, the methods applied include the SWOT method (Strength, Weakness, Opportunities, Threat) and are designed using PHP and MySQL programming as a database.